The Vernacularization of Science, Medicine, and Technology in Late Medieval Europe: Broadening Our Perspectives - Crossgrove, William (Early science and medicine, 2000)
The "vernacularization" of medieval texts dealing with scientific subjects was a more complicated process than earlier views would suggest. While popularizations were certainly important, some vernacular texts were written for specialists (especially in medicine). Certain texts describing practical knowledge had no Latin original to draw from or relied on models from Antiquity quite unrelated to contemporary practice. Their study is further complicated by the state of research, which in some cases is relatively good (e.g. treatises on hunting) but in others doesn't even allow for a preliminary overview (e.g. surgeries). Other complicating factors are distribution (the limited circulation, e.g., of "encyclopedias" against the presence of the ps.-Aristotelian Secreta Secretorum in all languages) and the availability of inventories, Middle Dutch and Middle English texts being the best documented. The essay concludes on some speculations about the similarity between contemporary English and Medieval Latin as scientific languages, and possible future developments.